Romanian version of SDM-Q-9 validation in Internal Medicine and Cardiology setting: a multicentric cross-sectional study - Baicus Cristian; Balanescu Paul; Gurghean Adriana; Badea Camelia Georgeta; Padureanu Vlad; Rezus Ciprian; Mitu Florin; Jurcut Ruxandra; Balanescu Andra Rodica; Daha Ioana; Balanescu Eugenia; Bojinca Mihai; et al. (Sciendo, 2019)
Background. Shared decision making (SDM) is becoming more and more important for the patient-physician interaction. There has not been a study in Romania evaluating patients' point of view in the SDM process yet. Therefore, the present study aims to evaluate the psychometric parameters of the translated Romanian version of SDM-Q-9.